Mobilisation of endogenous haematopoietic stem cells and their use as treatment for subacute stroke - England, Timothy John (2012)
The potential application for stem cell therapy is vast. Despite a limited understanding of their mechanisms of action, clinical trials assessing stem cells in human stroke are underway. Colony stimulating factors (CSF) such as granulocyte colony stimulating factor (G-CSF), which have been used to mobilise haematopoietic stem cells (HSC), also show promise in treating stroke.